2015
DOI: 10.1007/s10834-015-9465-0
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Instability and Housing in Low-Income Families’ Residential Mobility

Abstract: Given the repercussions of residential mobility, increased understanding of correlates of mobility is important for efforts to support family well-being. Using survey data on low-income families from the Three City Study (N = 2393), multilevel mixed longitudinal analyses examined factors associated with family residential mobility across the domains of family instability, housing and neighborhood contexts, and family characteristics. Results revealed contributions of family instability and housing and neighbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…Change of residence, a stress-generating event in itself for both parents and children, is likely to affect daily family routine, and also create some disruptions in the social network. Seeing as moving is often compounded by other events such as transitions in parents’ intimate partner relationships or job changes (Kull, Coley, & Lynch, 2016), the greater residential instability observed in mothers who broke the cycle of maltreatment might denote a certain difficulty achieving stability more generally in their lives.…”
Section: Discussionmentioning
confidence: 99%
“…Change of residence, a stress-generating event in itself for both parents and children, is likely to affect daily family routine, and also create some disruptions in the social network. Seeing as moving is often compounded by other events such as transitions in parents’ intimate partner relationships or job changes (Kull, Coley, & Lynch, 2016), the greater residential instability observed in mothers who broke the cycle of maltreatment might denote a certain difficulty achieving stability more generally in their lives.…”
Section: Discussionmentioning
confidence: 99%
“…Family structure is known to be both a driver and a consequence of economic inequality more broadly (McLanahan & Percheski, ). Most of what we know about family structure and economic well‐being relates to how discrete changes, such as divorce or relationship dissolution, affect family income (e.g., Avellar & Smock, ; Holden & Smock, ), but changes in family structure could alter economic circumstances in multiple ways, including access to health insurance (Peters, Simon, & Taber, ), residential mobility (Kull, Coley, & Lynch, ), and material hardship (Heflin, ).
As work became less stable, so too did family structure as a result of changes in marriage, cohabitation, and divorce rates
…”
Section: Causes Of Economic Instabilitymentioning
confidence: 99%
“…Work-family life balance that working mothers try to achieve can be easily sabotaged by housing instability. Kull et al ( 2016 ) reported that higher residential mobility was associated with changes in employment status and relationships, experiences of intimate partner violence, as well as private-market rentals, substandard housing, and bad neighborhoods.…”
Section: Families In Poverty: Decade In Reviewmentioning
confidence: 99%